Reliability and validity of the ankle inversion discrimination apparatus during walking in individuals with chronic ankle instability - Shao, Xuerong; Kang, Ming; Luan, Lijiang; Deng, Fawei; Adams, Roger; Wu, Tao; Han, Jia (Frontiers in Physiology, 2023)
Purpose: 1) to explore the test-retest reliability of a new device for measuring ankle inversion proprioception during walking, i.e., the Ankle Inversion Discrimination Apparatus—Walking (AIDAW) in individuals with or without Chronic Ankle instability (CAI); 2) to assess its discriminant validity in differentiating individuals with or without CAI; 3) to investigate its convergent validity by examining its association with Cumberland Ankle Instability Tool (CAIT) and the Y Balance Test (YBT). Methods: For test-retest reliability, 15 participants with CAI and 15 non-CAI healthy controls were recruited. Participants completed the AIDAW test twice with a 7-day interval. The area under the receiver operating curve (AUC) was obtained as the AIDAW score. The intraclass correlation coefficient (ICC) and MDC90 were calculated. For the validity study, another 20 individuals with CAI and 20 non-CAI healthy controls were involved. The AIDAW scores were analyzed by an independent samples t-test, and the optimal cutoff value of AIDAW scores to best distinguish individuals with CAI was calculated by Youden’s index. Spearman or Pearson correlation analysis was used to analyze the correlation between AIDAW proprioceptive scores and the CAIT and final YBT scores. Results: For test-retest reliability, the ICC values for the CAI, non-CAI, and the whole group were 0.755, 0.757, and 0.761 respectively. The MDC90 of the CAI and non-CAI group was 0.04 and 0.05. Regarding discriminant validity, the AIDAW proprioceptive discrimination scores in the CAI group were significantly lower than those in the non-CAI group (p = 0.003); and the cutoff score for distinguishing CAI from the non-CAI participants was 0.759. For convergent validity, the AIDAW scores were significantly correlated with the functional balance YBT final scores (p = 0.001) and the CAIT scores (p = 0.009). Conclusion: The AIDAW is a reliable and valid device for evaluating ankle inversion proprioception during walking in individuals with and without CAI. AIDAW can be used as a clinical assessment tool to discriminate CAI from non-CAI individuals and to monitor effects of rehabilitation. The AIDAW proprioceptive discrimination scores were significantly and positively correlated with YBT and CAIT scores.